Stimuli-Responsive Dewetting/Wetting Smart Surfaces and Interfaces (Biologically-Inspired Systems,, 2018)
Superhydrophobic surfaces, artificially mimicking lotus leaves, have captured the attention of scientists and engineers over the past few decades. Recent trends have shifted from superhydrophobicity to superominipohobicity, or superamphiphobicity. In addition, dynamic rather than static surface wetting/dewetting properties, which can be triggered by various stimuli, including temperature, pH, magnetic/electric fields, solvents, light exposure etc, have been highly sought after for commercial applications. This book will focus on recent topics related to various stimuli-responsive wetting/dewetting surfaces, and give an overview of the knowledge and concepts of how to design and establish these smart artificial surfaces, which can be used for technical developments in a wide variety research fields.